Conceptions, functions and actions: teaching music musically - Mills, Janet (REVISTA DA ABEM, 2014)
Clearly, the organisation of music education varies widely between countries. However,global values of music education include that music is taught “musically”. Music education is musicmaking: composing, performing and listening. It is not learning about music: the names of orchestralinstruments, or the decoding of staff notation. In England, as in all countries, we have some examplesof very fine musical teaching. Some of this work is idiosyncratic. Examples include a 9-13 schoolwhere the pupils used descant recorder as a medium for composing and performing, that culminatedin jazz where everyone “soloed”. In a 13-18 mixed school, boys began using their voices as amedium, just as their voices began to change. We also have examples of teaching that is poor. Thecauses may include published schemes of work; bandwagons; dogma; not daring to be different;the difficulty of analysing one’s own teaching; the difficulty of analysing one’s own musicaldevelopment; and underexpectation of students’ musical development. In the UK we have growingnumbers of primary and secondary teachers who teach music musically. But we still have much tolearn from other countries